Prevalence of overweight, obesity and its associated risk factors among school children aged 6-16 years of Biratnagar - Sah, Vijay Kumar; Giri, Arun; Acharya, Rupak (Journal of Nobel Medical College, 2016)
Background The World Health Organization (WHO) defines obesity as a ‘global epidemic. Overweight and obese children are at higher risk for developing long-term chronic diseases like hypertension. With globalization bringing more lifestyle modifications, adolescents are exposed to multiple risk factors including obesity, diet, academic stress, lack of physical work apart from hereditary risk factors. Early diagnosis of obesity and hypertension is an important strategy in its control, effective treatment and prevention of complications. The aim of the study is to assess the prevalence of and the factors associated with childhood overweight/obesity among school children Material and Methods It is a school based cross sectional study done in schools of Biratnagar. School going children aged 6 to 16 years from 10 different schools of Biratnagar were taken as study population. Five were private schools and five were government schools. All the school going children aged 6 to 16 years were included in the study. Children with any chronic illness were excluded from the study. Results A total of 1900 students were included between age group of 6 to 16 years. The prevalence of overweight, obesity and hypertension were 2.9%, 1.8% and 6.1%. Conclusion Overweight, obesity was significantly associated with hypertension. Students studying in private schools and family income > Rs.10,000 were strongly associated with overweight, obesity and hypertension. Family history of hypertension was also associated with overweight/obesity. Journal of Nobel Medical College Vol.5(2) 2016; 22-25